Ivermectin attenuates Schistosoma japonicum-induced liver fibrosis and is associated with downregulation of YAP signaling - Xuan, Minhui; Zhang, Peiru; Guo, Jiale; Guan, Fei; Lu, Shengjun; Liu, Wenqi (Frontiers in Cellular and Infection Microbiology, 2025)
Liver fibrosis caused by schistosomiasis is mainly driven by hepatic stellate cell (HSC) activation and excessive extracellular matrix deposition. Yes-associated protein (YAP), a central effector of the Hippo pathway, plays a critical role in HSC activation and liver fibrogenesis. This study investigated the antifibrotic effects of ivermectin, an antiparasitic reported to inhibit YAP, in Schistosoma japonicum-infected BALB/c mice. Mice were treated intraperitoneally with ivermectin (2 mg/mL) every two days for four weeks, starting four weeks post-infection. Primary HSCs and Kupffer cells were isolated, and LX-2 cells stimulated with soluble egg antigen (SEA) were treated with ivermectin or cocultured with Kupffer cell supernatants. Histological analysis revealed that ivermectin markedly reduced granuloma formation and collagen deposition. Ivermectin suppressed HSC activation markers, fibrosis-related gene expression, and YAP levels, promoting cytoplasmic retention of phosphorylated YAP. It also reduced arginase-1 and profibrotic markers in Kupffer cells and decreased profibrotic factor secretion in coculture assays. These results demonstrate that ivermectin attenuates S. japonicum-induced liver fibrosis and modulates YAP signaling as well as profibrotic activity, highlighting its therapeutic potential in S. japonicum infection.